1992
DOI: 10.1002/oms.1210271024
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen–carbon, carbon–carbon double rearrangement induced by proximity effects. Part 3: Essential structural requirements in methoxydiphenylmethanes

Abstract: The hydrogen-carbon, carbon-carbon double rearrangement, responsible for the formation of benzyl or tropylium ions previously observed in the electron ionization mass spectra of several substituted 1,lbis(dimethoxydipheny1)methanes bearing an ortho methoxy group, also occurs for 2-methoxydiphenylmethane (1) itself, the simplest compound of the series. It was shown using deuterium and ''C labelled 2methoxydiphenylmethanes (2, 3) that in this instance benzyl or tropilium ions are also formed through two alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…In order to ascertain whether the peak at m/z 91 of 1 and 2 corresponds to the rearrangement ion b (Scheme ), we examined the CI (methane) mass spectra of isotopomers 1d 3 and 2d 3 (Figs 1(b) and 2(b), respectively). The complete shift to m/z 93 confirms the formation of the ion b by the double rearrangement reaction of diphenylmethyl cations, previously observed in electron ionisation mass spectra 1–4. The peaks due to anisole loss, at m/z 107 and 121 for 1 and 2 , respectively, are not shifted in the spectra of the isotopomers 1d 3 and 2d 3 .…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…In order to ascertain whether the peak at m/z 91 of 1 and 2 corresponds to the rearrangement ion b (Scheme ), we examined the CI (methane) mass spectra of isotopomers 1d 3 and 2d 3 (Figs 1(b) and 2(b), respectively). The complete shift to m/z 93 confirms the formation of the ion b by the double rearrangement reaction of diphenylmethyl cations, previously observed in electron ionisation mass spectra 1–4. The peaks due to anisole loss, at m/z 107 and 121 for 1 and 2 , respectively, are not shifted in the spectra of the isotopomers 1d 3 and 2d 3 .…”
Section: Resultssupporting
confidence: 86%
“…It has been reported that diphenylmethyl cations formed by the benzylic cleavage of the molecular ions of 1,1‐diphenylalkanes bearing, in the ortho position, an alkoxy, alkyl‐ or dialkylamino or alkylsulfanyl group undergo a double rearrangement process involving consecutively a H‐to‐C migration followed by a C‐to‐C displacement reaction1–4. The overall process affords benzyl (or tropylium) cations through migration of an alkylidene residue of the ortho ‐alkylhetero group to the other aromatic ring (Scheme ), and this constitutes a pathway for benzyl (or tropylium) cation formation not previously reported 5,, 6…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The isotopic effect indicates that the hydrogen migration affording the rearrangement ion a' is the rate-determining process, and the close values in 70 eV-(k H /k D = 1.4), 1,3 and in MIKE-(k H /k D = 1.6), 2 spectra agree with a loose transition state for the hydrogen migration. 8 In order to achieve detailed mechanistic insight and information on the arrangement of the transition state related to the process involving the hydrogen migration, the determination of substituent effects on the abundance of the benzyl ion formation process could be used as a valuable tool.…”
Section: Methodsmentioning
confidence: 83%
“…2,3 It has been unequivocally demonstrated by experiments with 2 H-and 13 C-labeled compounds that the whole process of benzyl ion formation involves migration of the methylene residue of the methoxy group linked to the 2-position of an aromatic ring (ring A) to the other aromatic ring (ring B). [1][2][3][4] Further investigation revealed that such a reaction occurs also for ortho-alkoxy derivatives (OEt, OiPr) by migration of an alkylidene residue other than methylene, as well as for ortho-alkyl-hetero (NHMe, NMe 2 , SMe) 1,1-diarylalkanes. 4 Finally, it has been determined that the formation of the benzyl-(or tropylium) ions b constitutes the main unimolecular decomposition reaction of ortho-alkylhetero-substituted diaryl-or alkyldiaryl-or triaryl-methyl cations, a, generated either under electron ionization 5 Step 1…”
Section: Introductionmentioning
confidence: 99%